Determinant of Indonesian Sovereign Retail Sukuk’s Return: Determinan Return Sukuk Ritel Negara Indonesia - Firsty Izzata Bella; Fitria Idham Chalid (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
Abstract: Retail Sukuk is one of the Islamic investment instruments that Muslim investors can choose in investing and can be used by the government as an alternative to financing the APBN deficit. This study aims to determine the effect of liquidity risk, inflation risk, and market risk on the return of Retail State Sukuk (SUKRI). A sampling of Retail Sukuk Series 009 (SR009) was conducted using the purposive sampling method with the consideration that the maturity of the series is the latest and can be traded on the secondary market. Through a multiple linear regression model with the Ordinary Least Square (OLS) analysis technique, the results indicated that simultaneously all independent variables (liquidity, inflation, and interest rates) had a significant effect on return (Yield). While partially the results have shown between each different variable where liquidity has a significant negative effect on yield, interest rates show a significant positive effect. In contrast, inflation has no significant effect on yield. The results of this study can be utilized as a reference for investors in making decisions to choose SUKRI as their investment portfolio because the yield can be viewed from both the liquidity of the Sukuk and macro-economics conditions such as inflation and interest rates. Hence, when the interest rate increases, the investor can decide to invest in SUKRI. In addition, the results of this study can be used as a consideration for the government in regulating risk management policies and determining the returns offered to SUKRI, which will be issued for the next series. Keywords: Sukuk Yield; Liquidity Risk; Retail Sukuk; Multiple Linear Regression. Abstrak: Sukuk ritel merupakan salah satu instrument investasi syariah yang dapat dipilih oleh investor muslim dalam berinvestasi dan dapat digunakan oleh pemerintah sebagai alternatif dalam membiayai defisit APBN. Penelitian ini bertujuan untuk mengetahui pengaruh risiko likuiditas, risiko inflasi, dan risiko pasar terhadap return Sukuk Negara Ritel (SUKRI). Pengambilan sampel Sukuk Ritel Seri 009 (SR009) dilakukan dengan menggunakan metode purposive sampling dengan pertimbangan jatuh tempo dari seri tersebut paling baru dan dapat diperdagangkan di pasar sekunder. Melalui model regresi linier berganda dengan teknik analisis Ordinary Least Square (OLS), hasil penelitian menunjukkan bahwa secara simultan semua variabel independen (likuiditas, inflasi, dan suku bunga) berpengaruh signifikan terhadap imbal hasil (Yield). Sedangkan secara parsial hasil yang ditunjukkan antara masing-masing variabel berbeda dimana likuiditas berpengaruh negatif signifikan terhadap Yield, suku bunga menunjukkan pengaruh positif signifikan, sedangkan inflasi tidak berpengaruh signifikan terhadap Yield. Hasil penelitian ini dapat dijadikan acuan bagi investor dalam mengambil keputusan untuk memilih SUKRI sebagai portofolio investasinya karena imbal hasil dapat ditinjau baik dari likuiditas Sukuk maupun kondisi makroekonomi seperti inflasi dan suku bunga. Sehingga, disaat suku bunga meningkat, maka investor dapat mengambil keputusan untuk berinvestasi di SUKRI. Selain itu, hasil penelitian ini dapat digunakan sebagai bahan pertimbangan bagi pemerintah dalam mengatur kebijakan manajemen risiko dan menentukan imbal hasil yang ditawarkan kepada SUKRI yang akan diterbitkan untuk seri selanjutnya. Kata Kunci: Yield Sukuk; Risiko Likuiditas; Sukuk Ritel; Regresi Linear Berganda